PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MEMBUAT PERANGKAT PEMBELAJARAN SD NEGERI 001 EMPAT BALAI KABUPATEN KAMPAR - Marzuki Marzuki (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is a classroom action research conducted at SD Negeri 001 Empat Balai, this research is basedon: (a) lack of ability of teacher in making learning device; (b) learning devices are only used as a complementand not for teaching needs; and (c) some teachers again if they are asked the learning device answer has no orhas not made it. Based on this research, researchers conducted research by applying the method of assigningtasks to improve the ability of teachers in making learning tools. This study was conducted in two cycles, eachcycle is implemented based on four stages: planning, implementation, observation, and reflection. The results ofresearch indicate that the ability of teachers in making learning devices increases. This is seen in the first cycleof 59% with good enough category and in the second cycle increased to 76% with Excellent category. Based onthis data, it can be concluded that the application of assignment method can improve teacher ability in makingSD Negeri 001 Empat Balai learning tool.